Citizenship Education in Self-Awareness and Tolerance : Implementation of Pancasila Values of College Students - Khriswina, Salwa Anggraeni; Nurizka, Rian (FKIP Universitas Lampung, 2024)
Abstract: Citizenship Education in Self-Awareness and Tolerance : Implementation of Pancasila Values of College Students. Objective: This study aims to describe the implementation of Pancasila values towards self-awareness and tolerance among UPY Pre-service elementary school teachers. Method: Using qualitative research with a case study approach. The subjects of UPY Pre-service elementary school teachers by interviewing semi-structured interviewees were analyzed using the Miles and Huberman data model. Findings: show that there is an implementation of Pancasila values to foster self-awareness and tolerance among fellow UPY Pre-service elementary school teachers in every class that has diversity of ethnicity, religion and daily culture. This is shown by the application of the pancasila precepts that have been applied in the classroom to appreciate every difference that exists. As a result, UPY Pre-service elementary school teachers have an attitude of awareness and tolerance towards others by respecting and respecting each other's differences side by side. Conclusion: Through pancasila education in this global era by applying and pouring it in the form of actions carried out daily and continuously is very effective in efforts to form an attitude of self-awareness and tolerance in students who are pluralism. Keywords: pancasila values, self-awareness and tolerance, college students.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202450